A metal–organic framework for oxidative desulfurization: UIO-66(Zr) as a catalyst. (1st December 2017) - Zhang, Xiaotian; Huang, Pengcheng; Liu, Aili; Zhu, Mingyuan
Highlights: We prepared UIO-66(Zr) catalysts and applied for oxidative desulfurization. The ODS desulfurization rate of DBT can reached 100% (500 ppm). The excellent performance was due to L acidic site of the catalyst. Abstract: Owing to the high prices and other shortcomings associated with the existing methods of complex catalyst preparation, we used the UIO-66(Zr) metal–organic frameworks to directly catalyze the oxidative desulfurization (ODS) reaction. The synthesized UIO-66(Zr) was characterized using nitrogen adsorption–desorption isotherm analysis, X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. Under optimal reaction conditions, the ODS conversion of dibenzothiophene (DBT) reached 100%. This excellent catalytic activity was attributed to the unsaturated coordination of Zr, which may produce beneficial Lewis acid sites.